Innovation as a Strategic Advantage in the Market on the Example of Jinwanhong Industrial - Xuejing Wang; Natalia Sakharchuk (Communications of International Proceedings, 2021)
The modern world poses new challenges for the economy as a whole and for each company separately. This dictates the need to change approaches to company management and look for new ways to solve strategic problems. Increased competition, global economic crises, geopolitical risks - all this affects the prospects for the company's development and its competitiveness. One of the solutions to existing difficulties is the use of innovation. Today, the concept of «innovation» has become a trend in all modern world business events, forums and government agendas, which reflects the desire of business to move to this level of development of its own management. For the implementation of innovations, it is important not only to understand the true meaning of this word, but also to objectively perceive the ability of a particular organization or structure to systematically produce real innovations. It is a serious understanding of «innovation» as a phased development of a company that will allow not in words, but in reality, to manage such a complex resource as innovation.
Keywords: Innovation; Innovation Strategy; Strategic Advantage; Competitiveness; Uniqueness; Economic Efficiency; Tea Company.